My Car Service Application (MCaSeP) - Application for Smart Reminder of Car Service - BINTI SULAIMAN, NUR ILYA ELLISYA; Dr. NAYEF ABDULWAHAB MOHAMMED ALDUAIS, (Applied Information Technology And Computer Science, 2023)
Malaysians continue to develop in all technical fields, especially in the area of information technology (IT), but there are still some people who may not understand the internal functions of the car, especially the car engine, and need the IT department to develop applications to help the community overcome this problem.  Project-related issues, which will improve the efficiency and capabilities of the car service application for all vehicle users and track the latest updates of their vehicle performance. Therefore, the main objective is to analyze, design, develop, test, and evaluate the performance of smart car service mobile application that related to the project scope for this application is mainly targeting the vehicle user among the teenager, women, students, and any parties that has less basic knowledge regarding the car purpose. The method used in this project is the Object-Oriented System Development Phase for planning the mission, commanding, and post-flight analysis which describes the fundamentals of software and system development. Based on the observation, the service application that provided the smart reminder for car service does not yet exist and the community needs the application that could help them to keep the car maintenance is useful for the long term. Therefore, this project is really important for vehicle users. MCaSeP application was successfully developed. In general, all stages of the application development process have been completed to achieve satisfactory objectives. In order to get the best performance of the application, the project needs to enhance the modules and maximize the functionality of the application.